One-time roasting method for reducing cracks of isostatic pressing graphite
The use of yellow sand and metallurgical coke with controlled thermal conductivity and electric heating in a step-wise process addresses the issue of cracking and uniformity in isostatic graphite production, enhancing product quality and efficiency.
Patent Information
- Application Number
- CN202411373627.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-20
AI Technical Summary
Existing methods for producing isostatic graphite result in high crack rates and poor uniformity, which affects the service life and safety of graphite products, particularly in semiconductor applications.
A one-time roasting method using a combination of yellow sand and metallurgical coke as auxiliary materials, with controlled thermal conductivity and particle size, along with electric heating and a step-wise heating process, to ensure uniform heat distribution and prevent cracking.
Reduces crack rates, increases residual carbon content, improves product uniformity and performance, and shortens production cycles while meeting the requirements for high-quality isostatic graphite used in semiconductors.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphite production, in particular to a one-time roasting method for reducing cracks in isostatic graphite. Background Art
[0002] Isostatic graphite is a high-performance special graphite material with the characteristics of electrical conductivity, high strength, high thermal conductivity and high uniformity. These characteristics make different grades of isostatic graphite widely used in various industries.
[0003] When graphite is processed into materials such as semiconductor heaters, crucibles and various structural support parts, the requirements for graphite's strength, purity and uniformity are particularly high. If the density and strength of graphite parts are too low, it is easy to crack during use, affecting the service life, and even worse, it is easy to cause accidents during the production process and cause serious losses. High-density graphite green billets are more likely to crack due to uneven heating during the first baking process, causing losses.
[0004] Based on this, various methods are used in the prior art to produce isostatic graphite-baked blanks, as follows:
[0005] Invention patent CN115246737A discloses a roasting method for preparing isostatic graphite products and the products thereof, wherein reaction gas is introduced during the roasting process to reduce the binder reaction, increase the product density, and shorten the roasting time. However, the reaction gas is introduced during the roasting process to inhibit the asphalt decomposition reaction and increase the density, but the blank is prone to internal cracking and scrapping without auxiliary material protection during the heating process. If auxiliary materials are used, it is difficult for the gas in the furnace cavity to contact the product surface to work.
[0006] Invention patent CN108640110A is a process for rapid roasting of high-end graphite materials, which combines the pressing and roasting processes. The blank is roasted using a resistance wire during the pressure holding process, and the pressure is released during the cooling process to shorten the overall production cycle. However, the production method that combines pressing and roasting can shorten the production cycle to a certain extent, but it is not suitable for isostatic pressing. The internal uniformity of the blank produced is poor, making it difficult to apply to the semiconductor industry.
[0007] In the method of coating and roasting carbon products in the invention patent CN103964415A, refractory wool is soaked in refractory slurry and loaded onto the product surface to reduce the escape of volatile matter and improve the density and strength of the product. However, the method of coating the green product with a refractory layer and roasting it can increase the residual carbon of the product and increase the density, but there is a risk of cracks: the shrinkage degree of the refractory layer is inconsistent with that of the green product, so the refractory layer is prone to gaps during the roasting process, causing the product to be heated and reacted unevenly, resulting in cracks.
[0008] Based on this, although the above-mentioned prior art can produce high-density isostatically pressed one-baked billets to a certain extent, there are still technical problems such as one-baked billets cracking and poor uniformity. Summary of the invention
[0009] The purpose of the present invention is to provide a one-time roasting method for reducing isostatic graphite cracks for the first time, so as to at least achieve the purpose of reducing one-time roasted blank cracks and improving the product quality rate.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] A one-time roasting method for reducing isostatic graphite cracks comprises the following steps:
[0012] S1. Furnace preparation;
[0013] S2. Barreling;
[0014] S201. First, a layer of yellow sand is laid on the bottom wall of the steel drum, and then an annular partition is loaded at the center of the steel drum, and then a layer of metallurgical coke is laid inside the annular partition, and then the product is coaxially loaded into the annular partition;
[0015] S202. First, metallurgical coke is loaded between the annular partition and the product until it is flush with the top of the product, and then a layer of metallurgical coke is laid on the top of the product and inside the annular partition. Then, yellow sand is loaded between the annular partition and the steel drum until it is flush with the top of the metallurgical coke. Then, the annular partition is pulled out, and finally, the empty space in the steel drum is completely filled with yellow sand;
[0016] S203. Load the steel barrel after the barrel filling into the bottom roasting furnace;
[0017] S3. Power supply for roasting;
[0018] S4. Cooling.
[0019] As one possible embodiment of the present application, in step S2, the room-temperature thermal conductivity of the yellow sand in various locations in the steel drum is greater than 1.5 W / (m·K); the room-temperature thermal conductivity of the metallurgical coke in various locations in the steel drum is less than 0.8 W / (m·K).
[0020] As one possible embodiment of the present application, the particle size of the metallurgical coke in each location in the steel drum is through a 50-mesh sieve, and the particle size of the yellow sand in each location in the steel drum is through a 100-mesh sieve.
[0021] As one possible embodiment of the present application, in step S2, the total thickness of the yellow sand and metallurgical coke laid under the product is greater than or equal to 200 mm; the thickness of the metallurgical coke loaded between the inner side of the annular partition and the product is 30%-70% of the total thickness of the metallurgical coke and yellow sand loaded between the inner side of the steel drum and the product.
[0022] As one possible embodiment of the present application, in step S2, the thickness of the yellow sand laid on the bottom wall of the steel drum and the yellow sand loaded on the side wall of the steel drum are the same; the thickness of the metallurgical coke laid on the bottom of the product, the metallurgical coke loaded on the side wall of the product and the metallurgical coke laid on the top of the product are all the same.
[0023] As one possible embodiment of the present application, in step S3, a step-by-step heating and heat preservation mode is used during power transmission, as follows:
[0024] In the range of RT-500℃, the temperature rise rate is 1-8℃ / h;
[0025] At 500℃, keep warm for 40-80h at ±1℃ / h;
[0026] Run at 500-target temperature ℃, with a heating rate of 1-5℃ / h;
[0027] Keep at target temperature at ±1℃ / h for 20-60h.
[0028] As one possible embodiment of the present application, in step S3, the roasting method is electric heating.
[0029] As one possible embodiment of the present application, in step S4, the steel barrel is inverted and taken out of the furnace after the temperature of the outer ring of the middle part of the steel barrel is lower than 150°C.
[0030] As one possible embodiment of the present application, during the operation of step S3 and step S4, the oxygen content in the furnace chamber is less than 0.1%.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. By using two auxiliary materials in the barrel filling process, the temperature can be homogenized multiple times to prevent the blank from being deformed too much during the roasting process and causing cracks; specifically, the use of a double auxiliary material layer of yellow sand and metallurgical coke can slow down the decomposition reaction of asphalt during the roasting process, increase the residual carbon content of the graphite-baked blank, and improve the structure and performance of the final graphite product.
[0033] 2. It is more difficult to control the quantity of barrels using two auxiliary materials than using a single auxiliary material. If natural gas heating and roasting are used, it is easy to cause a decrease in product uniformity. Therefore, it is improved to electric heating and roasting, which promotes a uniform distribution of the heat field in the furnace and can effectively control the heating process.
[0034] 3. After the barreling and roasting methods are improved in the present invention, the heating uniformity of the product is improved, which allows the use of a faster roasting curve and reduces the risk of cracks in the blank, thereby achieving the purpose of shortening the production cycle, saving costs, reducing the oxidation rate, and increasing the yield.
[0035] In summary, the present invention can effectively reduce the crack rate, increase the amount of residual carbon, improve product performance, reduce costs, shorten the cycle, and meet the requirements of isostatic graphite for semiconductors by improving the barrel loading and roasting heating process of the car bottom roasting furnace and optimizing the corresponding process parameters. Specifically, the isostatic graphite blank for semiconductors roasted by the present invention has a product quality rate increased from 80% to 90%, a weight loss rate reduced from 7.16% to 6%, an overall structure tends to be uniform, and a production cycle shortened by 20% compared with the original process. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 : Figure 1 This is a cross-sectional view of the steel drum when it is filled;
[0037] Figure 2 : Figure 1 A schematic diagram of the structure in the normal direction;
[0038] Figure 3 : Figure 1 A schematic diagram of a cross-sectional structure viewed from above;
[0039] Figure 4 : Schematic diagram of the structure of steel drums being loaded into a car bottom roasting furnace;
[0040] Figure 5 : Actual picture of roasted products;
[0041] Wherein, (a) is a photo of the calcined product in Comparative Example 1;
[0042] (b): Schematic diagram of the inner side crack structure in Figure (a);
[0043] (c) : Physical picture of the baked product in Example 1;
[0044] In the figure, 1- steel drum; 2- yellow sand; 3- metallurgical coke; 4- annular partition; 5- product. DETAILED DESCRIPTION
[0045] In the prior art, a roasting process often has the following technical defects when it is actually implemented:
[0046] First, if the roasting temperature rises too fast, it is easy to cause a large temperature difference between the inside and outside of the product, resulting in internal cracking;
[0047] Secondly, the uneven distribution of heat field during the roasting process may cause temperature differences at some locations on the surface of the blank, resulting in a decrease in uniformity, uneven shrinkage and cracks.
[0048] Third, during the roasting process, a large amount of smoke is released due to the reaction of the green product, which may cause hollow cracks in the green product or reduce its performance.
[0049] Based on this, the present invention provides a one-time roasting method for reducing isostatic graphite cracks, comprising the following steps:
[0050] S1 Preparation in the furnace: clean up the debris in the furnace and the steel drum, check whether the heating resistance wire in the furnace (the conventional process is to check the natural gas burner, which should be replaced after changing to electric heating), pressure gauge, oxygen content monitor and other equipment are in normal condition, and confirm whether the steel drum, annular partition, refractory bricks and other structural parts are aging, deformed or rusted;
[0051] S2 barreling.
[0052] S201. First, a layer of yellow sand is laid on the bottom wall of the steel drum, and then an annular partition is loaded at the center of the steel drum, and then a layer of metallurgical coke is laid inside the annular partition, and then the product is coaxially loaded into the annular partition;
[0053] S202. First, metallurgical coke is loaded between the annular partition and the product until it is flush with the top of the product, and then a layer of metallurgical coke is laid on the top of the product and inside the annular partition. Then, yellow sand is loaded between the annular partition and the steel drum until it is flush with the top of the metallurgical coke. Then, the annular partition is pulled out (the annular partition in the present invention is extremely thin, generally less than 1 mm, and the thickness of the auxiliary materials inside and outside the annular partition is almost not affected after it is taken out), and finally, the empty space in the steel drum is completely filled with yellow sand;
[0054] S203. Load the steel barrels after filling into the bottom roasting furnace one by one;
[0055] S3. Power supply roasting: After the barrel filling step is completed, the start-up program can be started to start heating, and the temperature can be raised and kept in a step-by-step manner;
[0056] S4 Cooling: After roasting, it enters the furnace cooling stage. During this period, pay attention to the oxygen content in the furnace chamber to prevent oxidation of the product.
[0057] In this application, compared with the existing roasting process, step S2 is improved from the green direct roasting / single auxiliary material steel barrel roasting process to two different functional auxiliary materials (i.e., yellow sand and metallurgical coke) barrel roasting. The two layers of auxiliary materials are loaded in layers through an annular partition, and they play different roles in the product roasting process. Among them, metallurgical coke can promote the stable and small amount of volatile components of the product, and prevent the temperature in the furnace from being conducted too fast; yellow sand can ensure that the heat is evenly covered on the surface of the steel barrel, and can fix the product to prevent it from deforming too much and causing cracks.
[0058] In order to reduce the cracks of the product, as one of the embodiments of the present application, the thermal conductivity of the yellow sand and metallurgical coke in the steel barrel is further limited, that is, in step S2, the room temperature thermal conductivity of the yellow sand in each place in the steel barrel is greater than 1.5W / (m·K); the room temperature thermal conductivity of the metallurgical coke in each place in the steel barrel is less than 0.8W / (m·K), and the standard deviation of the room temperature thermal conductivity of the two auxiliary materials is less than 20%. In this scheme, the performance of the auxiliary materials has a greater impact on the product. If the thermal conductivity of the auxiliary materials fluctuates greatly, the product is very likely to crack due to uneven heating inside and outside. Therefore, this application limits the thermal conductivity of the two auxiliary materials, which can prevent the technical problem of product cracking due to uneven heat transfer.
[0059] In order to reduce cracks in the product, as one of the embodiments of this application, the particle size of the yellow sand and metallurgical coke in the steel barrel is further limited, that is, the particle size of the metallurgical coke in each place in the steel barrel is through a 50-mesh sieve, and the particle size of the yellow sand in each place in the steel barrel is through a 100-mesh sieve. In this scheme, the auxiliary materials used for barreling are all calcined auxiliary materials, among which the metallurgical coke can promote the stable and small amount of volatile components of the product, and prevent the temperature in the furnace from being conducted too quickly; the yellow sand can ensure that the heat is evenly covered on the surface of the steel barrel, and can fix the product to prevent it from deforming too much and causing cracks.
[0060] In order to reduce cracks in the product, as one of the embodiments of the present application, the thickness of the auxiliary materials in various places in the steel drum is further limited, that is, in step S2, the total thickness of the yellow sand and metallurgical coke laid under the product is greater than or equal to 200mm; the thickness of the metallurgical coke loaded between the inner side of the annular partition and the product is 30%-70% of the total thickness of the metallurgical coke and yellow sand loaded between the inner side of the steel drum and the product, and the thickness of the yellow sand above the product is ≥ the thickness of the yellow sand below the product. The thickness of the yellow sand laid on the bottom wall of the steel drum is the same as the thickness of the yellow sand loaded on the side wall of the steel drum; the thickness of the metallurgical coke laid on the bottom of the product, the metallurgical coke loaded on the side wall of the product, and the metallurgical coke laid on the top of the product are all the same. In actual implementation, another difficulty in step S2 is the ratio of the two auxiliary materials. If the thickness of the auxiliary material layer is improperly set, it may cause uneven heating on the surface of the product, resulting in reduced product performance or cracks due to uneven shrinkage. Therefore, restrictions are imposed on the thickness of the auxiliary materials at various locations, which can not only ensure that the product is enhanced by the two auxiliary materials, but also prevent cracks caused by large changes in the auxiliary materials. At the same time, the heating source is changed in conjunction with a special roasting method, which greatly reduces the risk of cracks caused by the two auxiliary materials.
[0061] In order to reduce the cracks of the product, as one of the embodiments of the present application, the roasting method is further limited, that is, as one of the embodiments of the present application, in step S3, the roasting method is electric heating. Compared with the prior art, step S3 improves the heating method in the roasting process. In the prior art, ring furnaces and car bottom roasting furnaces are generally used, and the heating methods are all natural gas-blower heating. In order to cooperate with the improvement of steel drum barreling, the present invention changes the heating method to electric heating on the basis of the car bottom roasting furnace, and the burners symmetrically arranged above the original furnace cavity are changed to resistance wires evenly distributed on all surfaces of the furnace, thereby improving the uniformity of the thermal field in the furnace cavity. The burner cooperates with the fan to form an over-high temperature position in the furnace cavity, which is not conducive to the uniform roasting of the blank. In addition, after the improvement, the steel barrel needs to be raised to the center of the furnace cavity to effectively overcome the technical problem that some products are too close to the resistance wire and heat up too fast, resulting in uneven roasting. Compared with the natural gas-fan heating method, the electric heating method has higher costs, but compared with natural gas roasting, the electric heating shortens the production cycle and reduces the probability of product cracks, which can balance the costs. At the same time, according to the electric heating roasting method of the present invention, the density and strength of the blank can be improved, so it can eventually be transformed into a high-value-added semiconductor graphite material, and the overall benefits and cycle are improved to varying degrees.
[0062] In order to further improve the product quality and performance, as one of the embodiments of the present application, the range of the heating rate during power transmission is further limited, that is, in step S3, the step heating method is used during power transmission, as follows:
[0063] Within RT-500℃, operate at a heating rate of 1-8℃ / h; at 500℃, keep warm for 40-80h at a range of ±1℃ / h; within 500-target temperature℃, operate at a heating rate of 1-5℃ / h; at the target temperature, keep warm for 20-60h at a range of ±1℃ / h.
[0064] In this solution, step S3 is mainly used to cooperate with step S2. Compared with the prior art, the heating rate is increased, and the roasting is performed in a step-by-step heating and heat preservation process. The power transmission is operated at a low heating rate in the early stage, and the temperature is increased in a step-by-step manner after the mid-term heat preservation. After the high temperature stage, the temperature is increased and the final temperature is kept to balance the temperature difference. Compared with the prior art, the heating rate is increased and the production cycle is shortened.
[0065] In order to adapt the time for taking the inverted barrel out of the furnace, as one of the possible embodiments of the present application, the temperature for taking the inverted barrel out of the furnace is further limited, that is, in step S4, the inverted barrel is taken out of the furnace after the temperature of the outer ring of the middle part of the steel barrel is lower than 150°C.
[0066] In order to further reduce the oxidation of the product, as one of the embodiments of the present application, the oxygen content in the furnace chamber is further limited, that is, during the operation of step S3 and step S4, the oxygen content in the furnace chamber is less than 0.1%. After the present application is changed to electric heating, there is no need to deliberately control the oxygen content in the furnace, and it is only necessary to ensure that the oxygen content in the furnace chamber is less than 0.1% during the roasting and cooling process, which greatly reduces the risk of product oxidation.
[0067] Next, the specific roasting process of isostatic pressing and roasting is described in detail.
[0068] Example 1 (taking the original size blank to be processed as an example)
[0069] S1 Preparation in the furnace: clean up the debris in the furnace and the steel drum, check whether the equipment is faulty, check the deformation of the steel drum, if the deformation is too large, it needs to be replaced and installed in the furnace.
[0070] S2 barreling (the yellow sand used in various places in the steel barrel during the barreling process is the same yellow sand, and the metallurgical coke used in various places is the same metallurgical coke).
[0071] S201. Figure 1 As shown, a layer of yellow sand (about 100 mesh) with a thickness of 100 mm is first laid on the bottom wall of the steel drum, and then the annular partition is loaded at the center of the steel drum, and then a layer of metallurgical coke (about 50 mesh) with a thickness of 100 mm is laid inside the annular partition, and then the product (diameter is 70% of the steel drum) is coaxially loaded into the annular partition (that is, the product is loaded into the center of the steel drum);
[0072] S202. Figure 2 As shown, first load the metallurgical coke between the annular partition and the product until it is flush with the top of the product, then lay a layer of metallurgical coke on the top of the product and inside the annular partition, then load yellow sand between the annular partition and the steel drum until it is flush with the top of the metallurgical coke, then pull out the annular partition, and finally fill the empty space in the steel drum with yellow sand, as shown in FIG. Figure 3 As shown; wherein, the thickness of the auxiliary material inside and outside the annular partition is the same;
[0073] It is worth mentioning that: Figure 1-Figure 3 The middle is a schematic diagram of the structure after the steel drum is loaded. Because the partition has been pulled out before this, there is actually no dotted partition in the figure. The dotted partition is marked to better show the loading method, but there are some differences from the actual situation.
[0074] S203. After the barrels are loaded in accordance with the loading method of S201 and S202, the multiple steel barrels are loaded into the bottom roasting furnace one by one. Figure 4 shown.
[0075] S3 roasting: Electric heating roasting heats up quickly in the early stage, and then heats up at a low rate after the furnace cavity reaches a certain temperature, and then keeps warm in stages. After switching to electric heating, the heating rate is determined by the power supply. Compared with controlling the air-fuel ratio of the burner, the power supply can more intuitively control the furnace cavity temperature. The specific roasting heating rate is related to the product specifications, formula and pre-process technology, as shown in the reference process table 1.
[0076] Table 1:
[0077] Temperature range / ℃ Heating rate℃ / h RT-100 5 100-300 2 300-500 1 500-500 Heat preservation 60h 500-700 2 700-900 3 900 Keep warm for 40 hours
[0078] In the roasting process, compared with the natural gas-blower heating process, electric heating can make the product heated more evenly. Specifically, the resistance wires are evenly distributed on the surrounding furnace walls and the top and bottom, and the refractory bricks are placed at the four corners under the steel barrel to ensure that the steel barrel is at the center height of the furnace chamber. Due to the use of metallurgical coke-yellow sand auxiliary materials, the heat is transferred to the product more evenly than the conventional process (the total amount of heat transfer is no different from the original process, mainly because the heat can be evenly transferred to the product. The cracks in the conventional process products are mainly caused by excessive heat transfer in some stages. The slow heat transfer is superficial, and the internal is uniform heat transfer). Combined with the electric heating and roasting method, the roasting curve for the same blank can be accelerated. The roasting curve of this application is about 25 days, and the conventional natural gas car bottom roasting furnace heating curve is about 30 days. Compared with the conventional roasting curve, the roasting curve of this application is shortened by about 20%, and the product crack rate is reduced. At the same time, after changing to electric heating, it can be ensured that the oxygen content in the furnace is lower than 0.1% during the roasting process, and the blank will not oxidize during the roasting process.
[0079] S4 Cooling: After the final temperature holding time is over, the furnace cooling can begin. When the steel drum temperature is less than 150°C, the drum can be turned over. In this embodiment, the cooling cycle is estimated to be about 20 days.
[0080] The isostatically pressed graphite blank prepared in this embodiment is shown in the figure. Figure 5 As shown in (c), it can be seen that the baked product has no obvious cracks, which further illustrates that the baking process provided by the present invention can increase the heating uniformity of the product and prevent the rapid conduction of heat to the blank product to cause temperature difference.
[0081] Example 2
[0082] Compared with Example 1, the ratio of the thickness of the auxiliary material on the inner side of the annular partition to the thickness of the auxiliary material on the outer side is adjusted to 4:6.
[0083] The remaining parameters and processes are the same as those in Example 1.
[0084] The isostatically pressed graphite blank prepared in this embodiment has no obvious cracks. Figure 5 (c) in .
[0085] Comparative Example 1
[0086] Existing technology: When filling barrels, all auxiliary materials are yellow sand; and natural gas roasting is adopted.
[0087] The isostatically pressed graphite blank prepared in this comparative example is Figure 5 As shown in (a), cracks occur at the end of the product, causing losses, where: Figure 1 The internal morphology of the crack in Figure 5 As shown in (b) in .
[0088] As shown in Figure (a), a baked product prepared by conventional technology is heated unevenly inside and outside, and cracks are generated from the end of the product and extend to the side to cause cross cracks.
[0089] As shown in Figure (b), the internal crack morphology of a baked blank is complex and there are stacking faults. It can be seen that due to uneven heat transfer, some blanks are heated faster, resulting in cracks.
[0090] In addition, the weight loss rate of the baked dough in Example 1, Example 1 and Comparative Example 1 was tested, and the test results are shown in Table 2.
[0091] Table 2:
[0092]
[0093]
[0094] It can be seen from Table 1 that the calcination weight loss in Example 1 and Example 2 is improved, and the residual carbon content inside the product is increased; overall, the average weight loss rate of Example 1 and Example 2 is 0.5% higher than that of Comparative Example 1, so the density strength is increased, and the internal structure of the product becomes more uniform, and the final high-density graphite product has better performance.
[0095] In summary, the present invention improves the prior art and can not only effectively improve the density and strength of a baked blank, but also reduce cracks on this basis and improve product performance.
[0096] In addition, according to the roasting process of Examples 1 and 2, the genuine product rate can reach 90% or more, while the roasting process in Comparative Example 1 can only reach 80%. The criteria for judging genuine products are: 1. There are no cracks on the surface of the product, including but not limited to cross cracks, side cracks, web cracks, etc.; 2. The product has no damage or falling pieces, and the size of the roasted blank is larger than the size specified by the brand.
Claims
1. A primary roasting method for reducing cracks in isostatic graphite, characterized in that: The steps include: S1. Furnace preparation; S2. Barreling; S201. First, a layer of yellow sand is laid on the bottom wall of the steel drum, and then an annular partition is loaded at the center of the steel drum, and then a layer of metallurgical coke is laid inside the annular partition, and then the product is coaxially loaded into the annular partition; S202. First, metallurgical coke is loaded between the annular partition and the product until it is flush with the top of the product, and then a layer of metallurgical coke is laid on the top of the product and inside the annular partition. Then, yellow sand is loaded between the annular partition and the steel drum until it is flush with the top of the metallurgical coke. Then, the annular partition is pulled out, and finally, the empty space in the steel drum is completely filled with yellow sand; S203. Load the steel barrels after filling into the bottom roasting furnace one by one; S3. Power supply for roasting; S4. Cooling.
2. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: In step S2, the room-temperature thermal conductivity of the yellow sand in the steel drum is greater than 1.5 W / (m·K); the room-temperature thermal conductivity of the metallurgical coke in the steel drum is less than 0.8 W / (m·K).
3. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: The metallurgical coke in the steel drum shall pass through a 50-mesh sieve, and the yellow sand in the steel drum shall pass through a 100-mesh sieve.
4. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: In step S2, the total thickness of the yellow sand and metallurgical coke laid under the product is ≥200mm; the thickness of the metallurgical coke loaded between the inner side of the annular partition and the product is 30%-70% of the total thickness of the metallurgical coke and yellow sand loaded between the inner side of the steel drum and the product.
5. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: In step S2, the thickness of the yellow sand laid on the bottom wall of the steel drum and the yellow sand loaded on the side wall of the steel drum are the same; the thickness of the metallurgical coke laid on the bottom end of the product, the metallurgical coke loaded on the side wall of the product and the metallurgical coke laid on the top end of the product are all the same.
6. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: In step S3, the step heating and heat preservation mode is used during power transmission, as follows: In the range of RT-500℃, the temperature rise rate is 1-8℃ / h; At 500℃, keep warm for 40-80h at ±1℃ / h; Run at 500-target temperature ℃, with a heating rate of 1-5℃ / h; Keep at target temperature at ±1℃ / h for 20-60h.
7. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: In step S3, the roasting method is electric heating.
8. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: In step S4, the steel drum is inverted and taken out of the furnace after the temperature of the outer ring in the middle of the steel drum is lower than 150°C.
9. A primary roasting method for reducing cracks in isostatic graphite according to claim 1, characterized in that: During the operation of step S3 and step S4, the oxygen content in the furnace chamber is less than 0.1%.
Citation Information
Patent Citations
Once roasting mixed type filling material for roasting furnace
CN102795857A
Graphitizing method for isostatic graphite product
CN104477891A
Isotropic isostatic pressing graphite material prepared through oxidized graphene and preparing method
CN106564894A
Isotropic isostatic pressing formed graphite material and preparation method thereof
CN109369184A
Application of graphitization furnace to roasting process
CN109626369A
